Caught in the Middle East : U.S. policy toward the Arab-Israeli conflict, 1945-1961 - Hahn, Peter L. (University of North Carolina Press, 2004)
"As is all too clear today, American postwar efforts to ameliorate Arab-Israeli relations before they could damage American interests in the Middle East failed to achieve a lasting peace and entangled the United States in the conflict in complex ways. Peter L. Hahn explores the strategic, diplomatic, political, and cultural factors that influenced the policies of Presidents Harry S. Truman and Dwight D. Eisenhower as they confronted the origins and escalation of one of the modern world's most intractable disputes."--Jacket